One-Pot Self-Assembled, Reduced Graphene Oxide/Palladium Nanoparticle Hybrid Aerogels for Electrocatalytic Applications. (20th October 2015) - Yun, Sol; Lee, Sangmin; Shin, Changhwan; Park, Sungjin; Kwon, Seong Jung; Park, Ho Seok
Graphical abstract: Highlights: 3D macroporous graphene/palladium nanoparticle hybrid aerogels are in-situ synthesized. Palladium nanoparticles are deposited on the surface of 3D macroporous graphene aerogels. 3D macroporous graphene/palladium nanoparticle hybrid aerogels show the hierarchical porosity. 3D macroporous graphene/palladium nanoparticle hybrid aerogels obtain good electrocatalytic activity. Abstract: Despite the synergistic features arising from three-dimensional (3D) interconnected porous networks and constitutive reduced grpahene oxide (rGO) sheets, the one-pot synthesis and self-assembly of metal nanoparticles (NPs) deposited on the 3D rGO aerogels (GAs) is still challenging. Herein, we demonstrate the in-situ synthesis and direct deposition of 3D macroporous GA/palladium (Pd) NP hybrids for electrocatalytic applications. The discrete Pd NPs with a narrow size distribution of 8 to 10 nm are uniformly distributed onto the pore surface of GAs, while 3D macroporosity being constructed via a one-pot, hydrothermal process. The morphology, chemical composition and structure, and textural property of the 3D GA/Pd NP hybrids are comprehensively characterized. As a consequence of the coupling effect of the hierarchical porosity and the discrete Pd NPs, the 3D GA/Pd NP hybrids exhibit the greater electrocatalytic activity compared to those of 3D GAs and 2D rGO/Pd NP hybrids.